Cyclic response of concrete frame with precast column and U-shaped composite beam. (September 2022) - Hu, Xinyu; Xue, Weichen; Zhang, Bin
Abstract: This paper aims to characterize the cyclic response of the two-storey and two-bay concrete frame with the precast column and U-shaped composite beam. 1/3-scaled cyclic tests were carried out where the axial compression ratio of centrality and edge columns was fixed as 0.3 and 0.2, respectively. Results showed that the failure of the precast frame and monolithic reinforced concrete (RC) frame to compare was governed by the crushing of concrete at column bases, showing a beam sidesway failure mechanism. The plump hysteresis loops were detected, and the overall displacement ductility of both frames was up to 4.3. The load-carrying ability, displacement ductility and energy dissipation capacity of the proposed precast frame were comparable to those of the monolithic RC frame. In addition, the numerical simulation successfully captured the failure pattern of such frames under cyclic loading, and the predicted load–displacement curves matched well with the experimental results. The parametric analysis including axial compression ratio, loading approach and composite beam type was also performed to extend the experimental work.